Age- and Sex-Associated Impacts of Body Mass Index on Stroke Type Risk: A 27-Year Prospective Cohort Study in a Low-Income Population in China - Gu, Hongfei; Shao, Shuang; Liu, Jie; Fan, Zhenqian; Chen, Yu; Ni, Jingxian; Wang, Conglin; Tu, Jun; Ning, Xianjia; Lou, Yongzhong; Li, Bin; Wang, Jinghua (Frontiers in Neurology, 2019)
The relationship between body mass index (BMI) and stroke type has remained controversial despite studies demonstrating that BMI is related to stroke risk, especially in specific groups. We assessed the age- and sex-associated impacts of BMI on stroke type in a low-income, poorly educated population in China. The association of BMI with stroke type was estimated using Cox regression analyses in this prospective cohort study, after adjusting for sex, age, education level, hypertension, diabetes, smoking and alcohol drinking status. During the follow-up period, 638 stroke cases occurred among the 3906 participants included in this prospective study. For men aged <65years, being overweight was an independent predictor of all stroke subtypes, compared with normal-weight individuals; the hazard ratios (HRs) and 95% confidence intervals (CIs) were 1.98 (1.52–2.58) for total stroke, 1.69 (1.22–2.33) for ischemic stroke, and 3.62 (2.09–6.25) for hemorrhagic stroke, all P<0.001. Being underweight was also an independent predictor of hemorrhagic stroke (HR, 5.10; 95%CI, 1.80–14.50, P=0.002). For women <65-years-old, being overweight was a risk factor for total (HR, 1.38; 95%CI, 1.01–1.89; P=0.044) and hemorrhagic (HR, 2.06; 95% CI, 1.00–4.28; P=0.050) strokes; obesity was a risk factor for total (HR, 2.47; 95% CI, 1.60–3.82) and ischemic (HR, 2.53;95%CI, 1.54–4.15) strokes, all P<0.001. These findings suggest that weight management should be a high priority for substantially reducing the heavy burden of strokes in rural China among both men and women <65-years-old; men<65-years-old should maintain their weight within a reasonable range.